The Influence Of Role Conflict, Job Satisfaction And Job Stress On Turnover Intention - Meilaty Finthariasari Finthariasari; Ririn Harini; Islamuddin Islamuddin; Henni Febriawati; Joey Ramadan Putra (UNIVED Press, 2024)
This type of research is quantitative research with a descriptive approach. The population of this study were all nurses at the As-Syifa Hospital in Manna City with a total sample of 52 people. Data collection was carried out using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 11.200 + 0.244 X1 - 0.201 X2+ 0.230 X3. The results of the analysis show that partially role conflict has a positive and significant effect on turnover intention (tcount = 3.963 and Sig = 0.000), job satisfaction has a negative and significant effect on purchasing decisions (tcount = -3.582 and Sig = 0.001) and work stress has a positive and significant effect on significant to turnover intention (tcount = 3.959 and Sig = 0.000). Simultaneously there is the effect of role conflict, job satisfaction and work stress on turnover intention (Fcount = 142.118 and Sig = 0.000).